CFD comparison of water based SiO2 nanofluid with benchmark MEA amine solution for CO2 capture through porous membrane contactor - Hadil Faris Alotaibi; Ahmed Mohsen; Bhavesh Kanabar; Abhinav Kumar; Nagaraj Patil; Debasish Shit; V. K. Bupesh Raja; Dhirendra Nath Thatoi; Deepak Gupta (Scientific Reports)
Abstract Abnormal emission of environmentally-hazardous greenhouse pollutants (mainly CO2) to the atmosphere have motivated global researchers to develop green, affordable and effective techniques to maximize their separation from different feed. To reach this aim, application of more effective and greener absorbing solutions is of great importance to decrease the harmful disadvantages of benchmark amine solutions like corrosion, eco-detriment and complexity of operation. In the current decades, nanofluids have shown great ability of application in membrane-based separation industries owing to their outstanding privileges like high specific surface area, great stability and feasibility of employment in both hydrophilic and hydrophobic membranes. The main novelty of this scientific investigation is the efficiency comparison of SiO2-based nanofluid with monoethanolamine (MEA) benchmark solution for CO2 capture in gas-liquid membrane contactor (MC) using CFD approach. Analysis of the results showed the approximately similar performance of SiO2-based nanofluid compared to MEA for separating CO2 (98.8% using SiO2-based nanofluid VS 99.5% using MEA). Despite lower efficiency, SiO2-based nanofluid can be well identified as an environmentally-friendly and efficient alternative absorbent for use in CO2-separation industries instead of chemically-detrimental MEA solutions. Additionally, effects of some membrane/module parameters like number of fibers, module length and gas velocity on the separation of CO2 are explained, comprehensively.